2022
DOI: 10.3390/app12115728
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Spatial Correspondence between Different Date Fruit Cultivars and Farms’ Cultivated Areas, Case Study: Al-Ahsa Oasis, Kingdom of Saudi Arabia

Abstract: Diversity in date palm (DP) cultivars plays a crucial role in the agroecosystems of several countries, such as the Kingdom of Saudi Arabia (KSA). This study aims to map and analyze the spatial distribution of the most grown DP cultivars (Khlas, Ruziz, and Shishi) in the Al-Ahsa oasis in the KSA and to highlight their spatial correlation with the corresponding cultivated patches within farms. Descriptive and spatial data on 288 farms were analyzed using GIS, data curation, cross-TAB statistics, clustering maps,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The climate of this region is subject to considerable variations across seasons and years. It is categorized by Mansour as being situated in the sub-tropical desert area, having cold, dry winters and very hot, dry summers, as per observation made by [31], winter occurs from November to March month, with an average temperature of around 22°C to 7.5°C meanwhile, from May to August, it lies in the range of 45°C and 24°C [30]. The country acknowledges the summer season as its hottest period.…”
Section: Study Area Descriptionmentioning
confidence: 98%
See 1 more Smart Citation
“…The climate of this region is subject to considerable variations across seasons and years. It is categorized by Mansour as being situated in the sub-tropical desert area, having cold, dry winters and very hot, dry summers, as per observation made by [31], winter occurs from November to March month, with an average temperature of around 22°C to 7.5°C meanwhile, from May to August, it lies in the range of 45°C and 24°C [30]. The country acknowledges the summer season as its hottest period.…”
Section: Study Area Descriptionmentioning
confidence: 98%
“…Positioned at an elevation of roughly 130 to 160 meters above sea level, it is sloping gradually towards the Gulf coast, between longitudes 49°30' to 49°50' E and latitudes 25°20' to 25°40' N. The shape of the oasis is somewhat similar to the English alphabet "L," with an axis length of around 30 km in the south-northeast direction and around 18 km from the west to the east. The total is 260 square kilometers [30]. The primary city in the region is Al-Hofuf City, located at the junction of two different axes at the southwest part of the oasis.…”
Section: Study Area Descriptionmentioning
confidence: 99%
“…The dates market in Saudi Arabia confronts various challenges that impact both domestic production and international trade. Among these challenges is the issue of water scarcity, which poses a significant obstacle to date palm cultivation due to the crop's high-water requirements and the country's limited water resources (Ismail et al, 2022). Moreover, climate change exacerbates this challenge, leading to unpredictable weather patterns, extreme temperatures, and heightened risks of pests and diseases, all of which adversely affect date palm health and productivity.…”
Section: Challenges For Dates Marketmentioning
confidence: 99%
“…Moreover, El-Sebaei and Al-Soliman (2018) indicated that the marketing margins of dates are significantly influenced by various factors depending on the cultivars studied, such as Khlas, Ruziz, and Shishi. These factors include the costs and methods associated with marketing, technical challenges related to transportation, packaging, sorting, and storage of dates, as well as behavioral aspects concerning knowledge of marketing methods, product quality, and pricing strategies (Ismail et al, 2022).…”
Section: Strategies To Increase Dates Exportmentioning
confidence: 99%
“…Al-Ahsa Oasis is the largest oasis in the kingdom of Saudi Arabia and located in the eastern region. The oasis covers a total area of 200 km 2 , of which more than 80 km 2 is under agricultural farming [31]. Al-Ahsa has a hot-dry climate, with summer temperatures reaching 46 • C, an evaporation rate of 2600 mm/year, and an annual rainfall rate of 80 mm [14,32].…”
Section: Study Areamentioning
confidence: 99%